1994
DOI: 10.1038/bjc.1994.25
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic trypsinogen and cathepsin B in human pancreatic carcinomas and associated metastatic lesions

Abstract: Summary Expression of pancreatic trypsinogen and cathepsin B in 23 surgically resected pancreatic ductal adenocarcinomas was evaluated immunohistochemically, using a monoclonal antibody against human pancreatic trypsinogen and a polyclonal antibody against human cathepsin B. Fifteen of 20 invasive tubular adenocarcinomas (75%) expressed pancreatic trypsinogen in a coarse granular pattern located in the supranuclear cytoplasm of the carcinoma cells. In addition, metastatic lesions, including those in peripancre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 27 publications
1
35
1
1
Order By: Relevance
“…It degrades a wide spectrum of extracellular matrix proteins (12) and activates proforms of other proteinases, including MMPs 1, 2, 8, 9, and 13 (13)(14)(15)(16). Tumor-associated trypsinogen-1 and trypsinogen-2 are strongly expressed in most ovarian cancers (17)(18)(19) and in several other cancers, e.g., pancreatic (20), gastric (21,22) and colorectal cancer (23,24), cholangiocarcinoma (25), and in esophageal squamous cell carcinoma (26). In ovarian cancer, expression of trypsinogen is associated with tumor aggressiveness (17,19), and in esophageal squamous cell carcinoma, it is strongly associated with recurrence and poor prognosis (26).…”
Section: Introductionmentioning
confidence: 99%
“…It degrades a wide spectrum of extracellular matrix proteins (12) and activates proforms of other proteinases, including MMPs 1, 2, 8, 9, and 13 (13)(14)(15)(16). Tumor-associated trypsinogen-1 and trypsinogen-2 are strongly expressed in most ovarian cancers (17)(18)(19) and in several other cancers, e.g., pancreatic (20), gastric (21,22) and colorectal cancer (23,24), cholangiocarcinoma (25), and in esophageal squamous cell carcinoma (26). In ovarian cancer, expression of trypsinogen is associated with tumor aggressiveness (17,19), and in esophageal squamous cell carcinoma, it is strongly associated with recurrence and poor prognosis (26).…”
Section: Introductionmentioning
confidence: 99%
“…PRSS2 may play a key role in tumor invasion by degrading a wide spectrum of extracellular matrix proteins (14) and activating other proteinases, including MMPs 1, 2, 8, 9 and 13 (15,16). PRSS2 has been reported to be highly expressed in several cancers, e.g., pancreatic (17), gastric (18), colorectal cancer (19), cholangiocarcinoma (20) and esophageal squamous cell carcinoma (21). The serum concentration of the inactive PRSS2 preproprotein was significantly higher in ovarian cancer patients with high stage compared to those with a low stage (22).…”
Section: Discussionmentioning
confidence: 99%
“…Metastatic peripancreatic neural plexuses and lymph nodes also stained intensely positive for trypsinogen. In addition, they stained positive for cathepsin B, but only weak to moderate (Ohta et al, 1994). In a more recent paper it has been shown that knockout of cathepsin B is associated with slowed PDAC progression, extended survival and decreased liver metastasis in a mouse model (Gopinathan et al, 2012).…”
Section: Role Of Premature Trypsinogen Activationmentioning
confidence: 98%